Another look at foreign aid - Gustav Ranis (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
The foreign aid landscape has undergone a paradigm shift in the last few decades, with changes in the behaviour of 'traditional' donors and a new focus on selectivity in aid disbursement, as well as 'new' donors and South-South co-operation playing an increasingly important role. Amidst these changes the debate over aid effectiveness rages on. What impact has aid had on recipient countries, and does aid really have the ability to induce policy reform? The structural adjustment loans of the 1980s were an attempt at prompting policy reform by imposing conditions on recipient countries. This proved ineffective for a number of reasons, and the aid community continues its search for the elusive 'silver bullet' in foreign aid provision. This paper assesses the past effectiveness of aid, comments on new aid donors and outlines some of the key arguments in favour of a potentially more effective and sustainable method of conditional aid delivery.
Keywords: C23; O1; O2; O4; 330; aid; conditional aid; donors; poverty reduction; economic growth; inequality